Membrane Proteins Production for Structural Analysis - Mus-Veteau, Isabelle.; Mus-Veteau, Isabelle. (Springer New York : Imprint: Springer, 2014)
This volume reviews the latest development in production, stabilization and structural analysis techniques of membrane proteins. It contains 14 chapters exploring topics including the advances in heterologous expression systems, stabilization tools and structural methods that contributed to the growing number of recombinant integral membrane protein structures solved in the past few years. Each chapter was written by internationally renowned scientists in the field of membrane proteins structural characterization. Membrane proteins account for roughly 30 percent of all open reading frames in fully sequenced genomes. However, to date, atomic structures have so far been obtained for only 424 integral membrane proteins, with 100 new structures determined in the last two years. Only 10 percent of the unique integral membrane protein structures are derived from vertebrates. In general, integral membrane proteins are present in tissues at very low concentration, making production of recombinant proteins in heterologous systems suitable for large scale production a prerequisite for structural studies. Since the first atomic structures of recombinant mammalian integral membrane proteins published in 2005 (the calcium ATPase SERCA 1A and a voltage-dependent potatium channel), the structures of 37 recombinant mammalian integral membrane proteins, from which 20 belong to the G Protein Coupled Receptors family, have been solved.